MORBIDITY AND MORTALITY ASSOCIATED WITH OBSTETRIC HYSTERECTOMY - Shaikh, Najma Bano; Shaikh, Shabnam; Shaikh, Jan Muhammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Obstetric hysterectomy still complicates a substantial number of pregnancies in third world countries and is a significant cause of obstetric morbidity and mortality. This study was carried out to evaluate in our setup the frequency of obstetric hysterectomy, its indication, risk factors, complication, morbidity, mortality and avoidable factors. Methods: A descriptive study of all patients who under went obstetric hysterectomy was conducted from 1st May, 2004 to 31st October, 2005 at Gynaecology and Obstetric Unit-II, III of Liaquat University of Medical and Health Science Hospital, Hyderabad. After collecting the data on pre-designed proforma the data was fed to SPSS in the form of frequency distribution tables and percentages were calculated. Statistical analysis of data was performed by using Chi-square test. The level of significance was taken as p<0.05. Results: During the study time period there were total 6495 deliveries and 41 cases of obstetric hysterectomy were identified, giving a frequency of 0.63% or 1 in 158 deliveries. Most of patients were from rural areas (82.92%), un-booked 73.17%), uneducated (95%), lower socioeconomical class (92.69%), 25-29 years age (48.78%) multiparae (56.10%), have to travel a distance of <100 km to reach hospital and referred late (51%) by healthcare providers (doctors). Majority of hysterectomies were performed due to ruptured uteri (51.21%). There were 5 maternal and 26 perinatal deaths; all were due to severity of conditions necessitating hysterectomy. Conclusion: Incidence of obstetric hysterectomy in our woman is very high. The reason being many avoidable factors such as high parity, inadequate maternity and family planning services, lack of proper referral system, un-booked status, mismanaged labour, illiteracy on the part of woman herself, family and health care providers are not taken care of during pregnancy, labour and puerperium. Keywords: Obstetric hysterectomy, multiparity, Injudicious use of oxytocics, uterine rupture, maternal morbidity and mortality